Cononsolvency of thermoresponsive polymers: where we are now and where we are going. Issue 15 (21st March 2022) - Bharadwaj, Swaminath; Niebuur, Bart-Jan; Nothdurft, Katja; Richtering, Walter; van der Vegt, Nico F. A.; Papadakis, Christine M.
Abstract : Overview of the recent developments focussing on the connection between cononsolvency and the preferential adsorption of the cosolvent. Discussion about the problems and challenges which are yet to be addressed. Abstract : Cononsolvency is an intriguing phenomenon where a polymer collapses in a mixture of good solvents. This cosolvent-induced modulation of the polymer solubility has been observed in solutions of several polymers and biomacromolecules, and finds application in areas such as hydrogel actuators, drug delivery, compound detection and catalysis. In the past decade, there has been a renewed interest in understanding the molecular mechanisms which drive cononsolvency with a predominant emphasis on its connection to the preferential adsorption of the cosolvent. Significant efforts have also been made to understand cononsolvency in complex systems such as micelles, block copolymers and thin films. In this review, we will discuss some of the recent developments from the experimental, simulation and theoretical fronts, and provide an outlook on the problems and challenges which are yet to be addressed.